Facial/sinus pain or pressure and migraine: exploratory findings from the HEADS registry - Kuruvilla, Deena E.; Tietjen, Gretchen E.; Panza, Gregory A.; Hodgkinson, Victoria L.; Godley, Frederick A. (Frontiers in Pain Research, 2025)
BackgroundRhinosinusitis (RS) is a leading reason for antibiotic prescriptions but treatment satisfaction is low. Misdiagnosis may contribute to poor outcomes, as migraine—often underrecognized—can mimic RS symptoms, with studies showing overlap between RS and migraine diagnoses. Our aims were to explore the demographics and clinical features of facial pain or pressure (FPP), its relationship with migraine and RS, and distinguish symptoms between these overlapping conditions.MethodsThe HEADS Registry, a web-based survey, targets adults with head and/or neck symptoms. Participants who answered “yes” (FPP+) or “no” (FPP−) to experiencing recurrent facial or sinus pain/pressure were included in this analysis. The ID Migraine screening tool was used to classify participants as ID Migraine+ or ID Migraine−. Demographics, symptoms, disability, history of allergies, sinusitis, and antibiotic use were compared between 1) FPP+ and FPP− groups, 2) FPP+/ ID Migraine+ and FPP+/ID Migraine−, and 3) FPP+/ID Migraine− and FPP−/ID Migraine+ subgroups. Continuous variables were compared using independent samples t-test or Mann–Whitney U, and categorical variables were compared using chi-square or Fisher's exact test.ResultsThe FPP+ group (n = 598) was younger, more often female, and reported higher rates of nasal, vestibular, and otologic symptoms compared to the FPP− group (n = 146). They also had more severe headaches, migraine-associated symptoms, and higher ID Migraine screening rates. The FPP+ group reported greater daily symptom interference, and more allergies, sinus infections, and antibiotic use. Those who screened positive for migraine (FPP+/ID Migraine+, n = 438) had more severe symptoms, greater disability, and more frequent forehead/eye pain. FPP+/ID Migraine− (n = 48) participants were more likely to report nasal symptoms, allergies, and sinus infections, while FPP−/ID Migraine+ (n = 85) participants reported more disabling headaches.ConclusionIn this exploratory analysis, FPP was strongly associated with headache, including migraine, as well as allergies, rhinosinusitis, and antibiotic use. The low reported effectiveness of antibiotics suggests potential misdiagnosis. Findings that migraine, plus autonomic, vestibular, otologic symptoms are associated with FPP, highlight the need to expand the differential diagnosis beyond infectious causes. These insights, along with ongoing registry improvements, will support efforts to refine diagnostic accuracy and optimize treatment strategies for neurologic, otologic, and rhinologic conditions.